NILAI TAMBAH AGROINDUSTRI GULA KELAPA - Jauhari, Zhiya Safni; Sundari, Ristina Siti; Heryadi, D Yadi (Universitas Galuh, 2023)
Coconut palm is a plantation commodity with high economic value; almost all parts can be utilized. One of them is coconut sap. Coconut sap is a clear liquid with a sweet taste produced from coconut flower bunches. If sold in raw form, coconut sap has a price of Rp. 350.00/kg, while if it is processed into coconut sugar products, it has a price of Rp. 12,000/Kg. Therefore, coconut sugar maker processes the sap to produce added value. This study aims to determine how much-added value and profit is generated in the coconut sugar agro-industry in Ciparakan Village, Kalipucang District, Pangandaran Regency. The method used is the case study method. The data analysis used is added value analysis. The results of this study indicate that the coconut sugar agro-industry in Ciparakan Village, Kalipucang District, Pangandaran Regency, can provide an added value of IDR 1,323 per kg of sap with an added value ratio of 69.02% which is included in a high added value ratio. The profit earned is IDR 1,073 per kg with a conversion factor 0.17.